An Intervention Study Using Cognitive Conflict to Foster Conceptual Change - Chow, Tuck-Choy; Treagust, David (SEAMEO Regional Centre for Education in Science and Mathematics, 2013)
The study involved evaluating the efficacy of a conceptual change instructional programme involving cognitive conflict in (1) facilitating form 2 (grade 8) students’ understanding of algebra concepts, and (2) assessing changes in students’ attitudes towards learning mathematics, in a mixed quantitative-qualitative research design. The results showed that there was significant improvement in students’ achievement in mathematics and students’ attitude towards inquiry of mathematics lessons. Enjoyment remained high even though enjoyment of mathematics lessons showed no change. Changes in students’ understanding (from unintelligible to intelligible, intelligible to plausible, plausible to fruitful) illustrated the extent of changes in their conceptions. Finally, recommendations for future research are proposed.